When it’s not safe to be me: employee authenticity mediates the effect of perceived manager psychopathy on employee well-being - Anna Sutton; Madeleine Stapleton (BMC Psychology, 2023)
Abstract Background Psychopathy in managers is often measured on global scales and associated with detrimental outcomes for subordinates, such as bullying and reduced well-being. Yet some features of psychopathy, like boldness, appear to have beneficial outcomes. Using the triarchic model of psychopathy, we differentiate between adaptive and maladaptive traits in managers and model their effects on employee engagement and burnout. In addition, we test the extent to which authenticity, known to ameliorate the effect of some negative experiences on well-being, might mediate the influence of managers’ perceived psychopathic traits on employee well-being. Methods In a two-wave study, full-time employees (N = 246) reported on their manager’s psychopathic traits (boldness, meanness, disinhibition), their own authenticity and, six weeks later, their engagement and burnout. Results In support of our hypotheses, manager boldness enhanced engagement and reduced burnout while meanness and disinhibition reduced engagement and increased burnout. Additionally, employee authenticity was a partial mediator of the effect of managerial psychopathy on engagement and burnout. Conclusions Perceived psychopathic traits in managers have the potential to influence whether employees feel able to be their authentic selves at work, which consequently affects their well-being. A work culture that values authenticity can directly improve well-being and help employees to deal with managerial behaviour that stems from maladaptive psychopathic traits. We also highlight the importance of discriminating between constituent psychopathic traits to identify the potentially adaptive nature of the boldness element of psychopathy.